PENGARUH LEVERAGE TERHADAP AUDIT REPORT LAG DENGAN PROFITABILITAS SEBAGAI VARIABEL MEDIASI PADA PERUSAHAAN IDX30 TAHUN 2015-2018 - Aritonang, Joice Idarumata; Siagian, Valentine (Buletin Studi Ekonomi, 2021)
This study is conducted with the aim of knowing the effect of leverage on audit report lag with profitability as a mediating variable. The population taken is IDX30 companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2018 period using the purposive sampling method. The number of samples used is 68 samples from 17 listed companies. The analytical method used in this research is descriptive statistical analysis, classical assumption test, and path analysis. The results obtained based on the tests that have been carried out are that leverage has a significant negative effect on audit report lag, which means that the higher the leverage, the lower the audit report lag. While profitability has no effect on audit report lag and leverage also has no effect on profitability. However, it was found that leverage had no significant effect on audit report lag through profitability mediation.